2020
DOI: 10.1111/apt.15733
|View full text |Cite
|
Sign up to set email alerts
|

Letter: suicide risk among adult inflammatory bowel disease patients. Authors' reply

Abstract: LINKED CONTENT This article is linked to Malham et al and Sánta papers. To view these articles, visit https://doi.org/10.1111/apt.15258 and https://doi.org/10.1111/apt.15708.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Malham et al followed the patients for a median of 10 years and reported an alarming four‐time higher risk of suicide in pIBD patients compared to controls. Suicide in pIBD was most common among young adults, a few years after transition to adult care, 45 and is consistent with a tendency of suicide rates increasing with age 46 . On the other hand, Kyllönen et al found no increased risk of suicide in patients with JIA, however, patients were only 15 years old at end of follow‐up.…”
Section: Discussionsupporting
confidence: 59%
“…Malham et al followed the patients for a median of 10 years and reported an alarming four‐time higher risk of suicide in pIBD patients compared to controls. Suicide in pIBD was most common among young adults, a few years after transition to adult care, 45 and is consistent with a tendency of suicide rates increasing with age 46 . On the other hand, Kyllönen et al found no increased risk of suicide in patients with JIA, however, patients were only 15 years old at end of follow‐up.…”
Section: Discussionsupporting
confidence: 59%